Symmetric matrix :
A square matrix A = |n,,] is called a symmetric matrix, if aij = aji for all i,j.
Example :
aij = aji for all i, j
⇒ (A)ij = (A')ij for ail i, j
⇒ A = A''

Skew-Symmetric Matrix :
A sqaure matrix A = [aij] is a skew symmetric matrix if A' = - A, that is aij = -aji or aij values of i and j.

a12 = 2, a21 = -2 ⇒ a12 = -a21
a13 = -3, a31 = 3 ⇒ a13 = -a31
and a23 = 5, a32 = -5 ⇒ a23 = -a32
It follows from the definition of a skew-symmetric matrix that A is skew-symmetric iff
⇒ aij = - aij for all i, j
⇒ (A)ij = “ (A')ij for all i, j
⇒ A = - A'
Thus, a square matrix A is a skew-symmetric matric if A' = -A.

Now, we are going to prove some results of symmetric and skew-symmetric matrices.
Theorem 1.
For any square matrix A with real number entries, A + A' is a symmetric matrix and A - A' is a skew- symmetric matrix.
Proof:
Let B = A + A', then
B' = (A + A')'
- A' + (A')' [As (A + B)' = A' + B']
= A' + A [As (A')' = A]
= A + A' [As A +B = B + A]
= B
Therefore B = A + A' is a symmetric matrix.
Now let C = A - A'
C'= (A - A')' = A' - (A')'
= A' - A = -(A - A') = -C
Therefore C = A - A' is skew-symmetric matrix.
Theorem 2.
Any square matrix can be expressed as the sum of a symmetric and a skew-symmetric matrix.
Proof:
Let A be a square matrix, then we can write
A = \(\frac{1}{2}\) (A + A') + \(\frac{1}{2}\) (A - A')
From the Theorem 1, we know that (A + A') is a symmetric matrix and (A - A') is a skew symmetric matrix.
Since, for any matrix A, (kA)' = kA', it follows that \(\frac{1}{2}\) (A + A') is a symmetric matrix and \(\frac{1}{2}\) (A - A') is a skew symmetric matrix. Thus, any square matrix can be expressed as the sum of the symmetric and a skew symmetric matrix.